Analysis of fermentation characteristics in fermented grains across seven rounds of sauce-flavored Baijiu: Microbial communities structure, physicochemical parameters, volatile and non-volatile flavor compounds - Xiaomin Liu; Yingchun Mu; Xiangxiang Lv; Nuo Chen; Lei Chen; Tangzheng Wen; Wei Su (Food Chemistry: X)
Pit fermentation is the critical stage for flavor formation in sauce-flavored Baijiu (SFB). This study aimed to elucidate the fermentation characteristics in fermented grains at the start (EP) and at the end (OP) of pit fermentation across seven rounds of SFB. Kroppenstedtia and Issatchenkia gradually replaced Pseudomonas and Pichia in EP, while Lactobacillus and Issatchenkia maintained dominance in OP. In both groups, volatile flavor compounds (VFCs) and moisture contents initially increased and then declined, non-volatile flavor compounds (N-VFCs) and starch contents overall decreased, and acidity, reducing sugar, and organic acid levels generally increased. Additionally, the VFC and N-VFC contents consistently increased from EP to OP within each round. Correlation analysis revealed Issatchenkia, Kroppenstedtia, Monascus, Virgibacillus, and Pichia significantly contributed to flavor compound. Finally, a metabolic network was constructed to predict microbial and flavor compound metabolic pathways. This study provided insights into the fermentation characteristics of SFB from a multi-dimensional perspective.